The bells in their silence : travels through Germany - Gorra, Michael Edward (Princeton University Press, 2004)
Nobody writes travelogues about Germany. The country spurs many anxious volumes of investigative reporting--books that worry away at the "German problem," World War II, the legacy of the Holocaust, the Wall, reunification, and the connections between them. But not travel books, not the free-ranging and impressionistic works of literary nonfiction we associate with V.S. Naipaul and Bruce Chatwin. What is it about Germany and the travel book that puts them seemingly at odds? With one foot in the library and one on the street, Michael Gorra offers both an answer to this question and his own trav